Simultaneous Nucleic Acids Detection and Elimination of Carryover Contamination With Nanoparticles-Based Biosensor- and Antarctic Thermal Sensitive Uracil-DNA-Glycosylase-Supplemented Polymerase Spiral Reaction - Wang, Yi; Jiao, Wei-wei; Wang, Yacui; Sun, Lin; Li, Jie-qiong; Wang, Ze-ming; Xiao, Jing; Shen, Chen; Xu, Fang; Qi, Hui; Wang, Yong-hong; Guo, Ya-jie; et al. (Frontiers in Bioengineering and Biotechnology, 2019)
The current report devised a novel isothermal diagnostic assay, termed as nanoparticles-based biosensor (NB)- and antarctic thermal sensitive uracil-DNA-glycosylase (ATSU)-supplemented polymerase spiral reaction (PSR; NB-ATSU-PSR). The technique merges enzymatic digestion of carryover contaminants and isothermal nucleic acid amplification technique (PSR) for simultaneous detection of nucleic acid sequences and elimination of carryover contamination. In particular, nucleic acids amplification and elimination of carryover contamination are conducted in a single pot, and thus, the use of a closed-tube reaction can remove undesired results due to carryover contamination. For demonstration purpose, Klebsiella pneumoniae (K. pneumoniae) is employed as the model to demonstrate the usability of NB-ATSU-PSR assay. The assay's sensitivity, specificity and practical feasibility were successfully evaluated using the pure cultures and sputum samples. The amplification products were detectable from as little as 100 fg of genomic DNAs, and from approximately 550 CFU in 1 mL of spiked sputum samples. All K. pneumoniae strains examined were positive for NB-ATSU-PSR detection, and all non-K. pneumoniae strains tested were negative for the NB-ATSU-PSR technique. The whole process, including rapid template preparation (20-min), PSR amplification (60-min), ATSU treatment (5-min) and result reporting (within 2-min), can be finished within 90-min. As a proof-of-concept methodology, NB-ATSU-PSR technique can be reconfigured to detect various target nucleic acid sequences by redesigning the PSR primer set.